Investigating Cultural Dimensions in EFL Textbook by Using Byram Checklist - Soni Ariawan (UIN Salatiga, 2020)
The present study is a content analysis that aims to investigate cultural dimension in an English textbook prescribed for senior high school in Indonesia which is officially published by the Ministry of Education and Culture in 2017. The data include 11 conversations, 17 reading texts, and 83 visual elements that are analysed qualitatively by employing Byram’s checklist. The findings show that stereotypes and national identity dominate the cultural dimensions with 28.05% and followed by social interaction and socialisation and life cycle with 15.9%. The occurrence of national geography is significant with 12.2%. However, social identity and social group, belief and behaviour, national history and social and political institutions are prescribed with less than 10%. The inclusion of various cultural dimensions has certain purposes. The inclusion of national identity, for instance, is pivotal for learners since the textbook is prescribed for senior high school students who are tremendously curious to determine their characters. This idea is aligned with the aim of the curriculum to facilitate the development of students with good character, good behaviour and strong nationality. It is concluded that the English textbook in Indonesia is on the way to its perfection in terms of proportionally represented cultural dimensions. However, the presence of various cultural aspects of the target culture and international target culture is also important to help students develop cultural competence and a certain level of respect as well as tolerance for others. Keywords: Textbook, cultural dimensions, cultural competence, national identity